The utilization of mangrove forests in ESD-oriented science learning to improve environmental literacy and science literacy: A meta-analysis - Triyanti Marfiana; Fenny Roshayanti; Intan Indiati; Siti Patonah (University of Muhammadiyah Malang, 2025)
The lack of utilization of the local environment in science learning causes low environmental and science literacy among students. In fact, integrating the surrounding environment, such as mangrove forests in Education for Sustainable Development (ESD) based learning is very important to foster scientific awareness and understanding from an early age. The aim of this research is to determine the use of mangrove forests in ESD-oriented science learning to improve environmental literacy and scientific literacy. This research is meta-analysis research with PRISMA methods. Data collection in research was carried out using documentation techniques through article search efforts using the Google Scholar search engine. The data sources in the research were 10 research journals from national journals with general criteria both in terms of educational level and research methods used. The data obtained was analyzed using quantitative data analysis with percentage results and qualitative data analysis in the form of descriptions of the studies studied. The results of the research show that utilizing mangrove forests in ESD-oriented science learning can increase environmental literacy and scientific literacy. Mangrove forests can be used as a learning resource for students at various levels of education starting from elementary/MI, middle/MTs, and high school. The use of mangrove forests in ESD-oriented science learning is able to answer learning problems experienced by teachers in integrating the local environment such as mangrove forests as a resource in science learning. By visiting the mangrove forest, students can make direct observations to learn about local ecosystems and research about biodiversity to increase environmental literacy and scientific literacy.